STUDY OF THE PREVALENCE OF Capillaria hepatica IN HUMANS AND RODENTS IN AN URBAN AREA OF THE CITY OF PORTO VELHO, RONDÔNIA, BRAZIL - Elierson José Gomes da Rocha; Sérgio de Almeida Basano; Márcia Maria de Souza; Eduardo Resende Honda; Márcio Botelho de Castro; Edson Moleta Colodel; Jéssica Carolinne Damasceno e Silva; Lauro Prado Barros; Elisa Sousa Rodrigues; Luís Marcelo Aranha Camargo (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Introduction: Hepatic capillariosis, caused by Capillaria hepatica (Calodium hepaticum) (Bancroft, 1893), Travassos, 1915 (Nematoda, Trichinelloidea, Capillariidae), is a common zoonosis in rodents but is rare in humans. Seventy-two cases in humans have been reported worldwide since the first case was described by MACARTHUR in 192417,27. This study aimed to determine the prevalence of Capillaria hepatica in humans and rodents in an urban area of Porto Velho, the capital of Rondônia, in Brazil. Methods: After conducting a census of the area, 490 residents were randomly selected, and, after signing a term of consent, provided blood samples that were screened for anti-Capillaria hepatica antibodies. Simultaneously, rats were captured to assess the prevalence of this parasite in rodents by histopathological examination in liver sections. Results: A prevalence of 1.8% was found among residents who had specific antibodies at a dilution of 1:150, indicating exposure to parasite eggs; 0.8% of the subjects also had positive titers at a dilution of 1:400, indicating true infection. The prevalence in rats was 2%. Conclusions: The prevalence of infection with this parasite among humans and rats was low. While the prevalence encountered among humans was within the limits reported in the literature, the prevalence among rodents was much lower.